The Sustainability of New Challenges in Smart City Planning in Palembang City: Keberlanjutan Tantangan Baru Perencanaan Kota Cerdas Di Kota Palembang - Ade Uswatun Hasanah; Feni Huspita Sari; Delfiazi Puji Lestari; Sutinah Andaryani (Jurnal Pemerintahan dan Politik, 2026)
Objective: This research aims to analyze the structural challenges and development of urbanization in Smart City planning in Palembang City and formulate an approach towards smart governance. Design/methodology/approach: The research uses a qualitative approach with a case study design. Data was collected through in-depth interviews, documentation studies and field observations, then analyzed using thematic analysis. Findings: The research results show that the main challenges do not lie in technological limitations, but in institutional fragmentation, digital gaps, and weak policy integration. Around ±50% of people still have limited access to digital public services, especially in suburban areas. These findings indicate that the Smart City approach in Palembang is still technology-driven and not fully governance-driven and is influenced by urbanization. Practical Implications: This research emphasizes the importance of a paradigm shift towards smart governance that is more inclusive, integrated and data-based. Practically, the results of this research provide recommendations for local governments to strengthen policy integration, equalize digital infrastructure, and increase community digital literacy. Originality/Value: Smart City planning in Palembang City is a strategic effort to utilize information and communication technology (ICT) to improve the quality of public services and government governance. However, previous research still tends to focus on technological aspects and has not studied in depth the institutional dimensions and social gaps in its implementation. Research Type: Research Article